In Silico Study of Betaine, Isoleucine, and DL-Stachydrine Compounds in Shipworm (Spathoteredo obtusa) Extract as an Antibacterial Agent of Aeromonas hydrophila - Andi Al Furqan; Fadjar, Mohamad; Maimunah, Yunita (Journal of Aquaculture and Fish Health, 2025)
The rapid increase in freshwater commodity production is accompanied by various obstacles that pose challenges for farmers, namely, disease infections. Bacterial infection by Aeromonas hydrophila is the pathogenic agent causing Motile Aeromonas Septicemia (MAS), which can result in 100% mortality within a short period. The AhlC toxin protein in A. hydrophila bacteria plays the most critical role in the Ahl tripartite toxin, as AhIC acts as a protomer and inserts itself into one membrane layer, then binds to AhlB and AhlA to form pores in both membrane layers. Active compounds found in marine mussel extracts (Spathoteredo obtusa), particularly betaine, isoleucine, and DL-stachydrine, have the potential to inhibit the AhlC toxin protein produced by A. hydrophila bacteria. This study aims to predict the interaction between the AhlC receptor protein in A. hydrophila bacteria and the active compounds identified from the extract of shipworms (S. obtusa) using molecular docking methods. The test results showed that all three compounds met all ADME predictions, with the best binding affinity value of -4.2 kcal/mol for isoleucine and DL-stachydrine, followed by -3.5 kcal/mol for betaine. Based on the test results, there are appropriate, stable, and effective hydrogen and electrostatic charge interactions with the ligand-receptor complex (ASN:32, GLN:35, ARG:112, and ASP:116), which play a crucial role as active sites in ligand binding to the receptor.